Analisis Kasus Microsoft V. United States (2018) : Implikasi Terhadap Hukum International - Mellinda Kharisty Mangulu; Lenny Husna (Prosiding, 2025)
The Microsoft v. United States (2018) case stands as a landmark in the discourse of international law concerning jurisdiction over digital data in the era of global information exchange. The dispute began when the U.S. goverment, thourgh the Federal Bureau Of Investigation (FBI), issued a warrant to microsoft to provide email data of a criminal suspect stored on its servers located in Ireland. Microsoft refused on the grounds that data stored outside the U.S. territory could not be accessed under the domestic legal framework, namely the Stored Communications Act (SCA) of 1986. This conflic ignited a global legal debate on data sovereignity and cross border privacy protection. This article aims to explore the jurisdictional conflict and the legal diplomatic response thourgh the enacment of the CLOUD Act. Using a normative juridical approach, the article also discusses the broader impact on internaational law, digital plomacy, and the strategic role of higher educations institutions in promoting digital legal literachy.